THE SCARECROW - Mayland, Abilawa Dyan; Kinasih, Widian Cahyo; Fadli, Insan; Nugroho, Bimo Basworo Her Kris; Permadi, Tian Rahmatullah (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Currently, the development of technology is already quite rapidly with many new discoveries were found, but of the many technologies invented yet applied or utilized for agriculture. Technology expulsion of rice pests automatically environmentally friendly (solar powered) with high efficiency is needed to save money, energy and time. In the study conducted to optimize the testing tool carefully gradually from the collection of materials and materials, design tools and programs, making tools, testing tools, data analysis and conclusions. To support this process and get the appropriate calculation is done using the first simulation software simulator with high accuracy. With the establishment of rice pest repellent technology automatically solar powered, could create an automated tool to repel pests of rice, rice pest population control, energy saving, power, cost, time, effective, practical, environmentally friendly and has a high efficiency in its use, so that farming communities can develop their business evolve towards better and produce maximum production of agricultural products.Â Keywords: Midges, automatic